Microwave‐assisted YBa2Cu3O7 precursors: A fast and reliable method towards chemical precursors for superconducting films. Issue 6 (20th March 2017) - Rijckaert, Hannes; De Roo, Jonathan; Roeleveld, Kevin; Pollefeyt, Glenn; Bennewitz, Jan; Bäcker, Michael; Lynen, Frederic; De Keukeleere, Katrien; Van Driessche, Isabel
Abstract: Highly stable, pure, and anhydrous organometallic YBa2 Cu3 O7‐δ (YBCO) precursor solutions were prepared by dissolving commercial YBCO powder in acetone by trifluoroacetic anhydride (TFAA) or a mixture of TFAA with propionic acid for low fluorine precursors. It is shown that compared to conventional oil bath heating reported in literature, the reaction to produce YBCO precursor occurs 72 times faster by microwave heating. More importantly, the formation of byproducts is suppressed, as shown by nuclear magnetic resonance (NMR) and mass spectrometry (MS). This approach allows a highly reproducible preparation of superconducting coatings which is of interest for low‐cost manufacturing processes capable of large‐scale production of the coated conductors via chemical solution deposition (CSD). This technology requires reliable and stable precursor solutions for continuous deposition. In this work, we obtained YBCO thin films on single‐crystal substrates ((100)‐LaAlO3 ) with a high critical current density ( J c ) of 3‐4 MA/cm² in self‐field at 77 K using TFA‐based YBCO precursors and J c of 5‐6 MA/cm² using low fluorine YBCO precursors.